Longer anogenital distance is associated with higher testosterone levels in women: a cross‐sectional study. (7th February 2014) - Mira‐Escolano, MP; Mendiola, J; Mínguez‐Alarcón, L; Melgarejo, M; Cutillas‐Tolín, A; Roca, M; López‐Espín, JJ; Noguera‐Velasco, JA; Torres‐Cantero, AM
<x xml:space="preserve">Abstract</x> Objective Animal models have suggested that anogenital distance (AGD) at birth reflects androgen levels during in utero development and predicts adult AGD. A recent study showed an association between perineal length and androgen levels in men, suggesting that serum testosterone levels in adulthood will depend on factors involved during the fetal period. The aim of this study is to assess the relationship between AGD measures and reproductive hormone levels in women. Design Cross‐sectional study conducted between February and November 2011. Setting University‐affiliated fertility clinics. Population 100 young college students. Methods Physical and gynaecological examinations were conducted on university students. All participants provided a blood sample for determination of reproductive hormones and completed an epidemiological questionnaire on lifestyles and gynaecological history. We used multiple linear regression analysis to examine the associations between perineal length measurements [anus‐fourchette (AGDAF) and anus‐clitoris (AGDAC)] and reproductive hormone levels. Main outcome measures Anogenital distance measurements and reproductive hormone levels. Results In the multiple linear regression analyses, AGDAF was positively associated with serum testosterone levels. Serum testosterone increased 0.06 ng/ml (95%CI 0.01, 0.10; P = 0.02) for each 1‐cm increase in AGDAF. None of the measurements was associated with other reproductive hormones. Conclusions Anogenital distance may predict normal reproductive development in women, and may be a new tool of potential clinical interest to evaluate ovarian function. Our results suggest that serum testosterone levels in adulthood may depend on factors operating in the prenatal period.